Digital Financial Transparency in Local Governments: The Role of Leverage, Dependency, and Fiscal Independence - Wicaksono, Ready; Utomo, Dwi Cahyo; Rohman, Abdul (Dinasti Publisher, 2026)
This study examines the influence of leverage, regional dependency, and regional independence on the disclosure of local government financial statements through internet-based reporting. The research employs a quantitative method with a causal approach using secondary data obtained from the financial statements of local governments in Kalimantan for the fiscal years 2018–2022. The sample was selected using purposive sampling, resulting in 30 observations. Data were analyzed using multiple linear regression analysis after passing classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The results indicate that leverage has a significant effect on the disclosure of local government financial statements through the internet. Regional dependency, however, does not significantly affect financial disclosure. Meanwhile, regional independence shows a significant positive effect on the disclosure of financial statements. These findings suggest that the financial characteristics of local governments, particularly leverage and fiscal independence, play an important role in encouraging transparency and accountability in internet-based financial reporting. The coefficient of determination shows that the independent variables explain 34.4% of the variation in financial disclosure, while the remaining variation is influenced by other factors not included in this study. This study highlights the importance of strengthening financial independence and improving financial management practices to enhance transparency in local government financial reporting.